(b+16)(b-18)=0

Simple and best practice solution for (b+16)(b-18)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (b+16)(b-18)=0 equation:


Simplifying
(b + 16)(b + -18) = 0

Reorder the terms:
(16 + b)(b + -18) = 0

Reorder the terms:
(16 + b)(-18 + b) = 0

Multiply (16 + b) * (-18 + b)
(16(-18 + b) + b(-18 + b)) = 0
((-18 * 16 + b * 16) + b(-18 + b)) = 0
((-288 + 16b) + b(-18 + b)) = 0
(-288 + 16b + (-18 * b + b * b)) = 0
(-288 + 16b + (-18b + b2)) = 0

Combine like terms: 16b + -18b = -2b
(-288 + -2b + b2) = 0

Solving
-288 + -2b + b2 = 0

Solving for variable 'b'.

Factor a trinomial.
(-16 + -1b)(18 + -1b) = 0

Subproblem 1

Set the factor '(-16 + -1b)' equal to zero and attempt to solve: Simplifying -16 + -1b = 0 Solving -16 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -1b = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -1b = 0 + 16 -1b = 0 + 16 Combine like terms: 0 + 16 = 16 -1b = 16 Divide each side by '-1'. b = -16 Simplifying b = -16

Subproblem 2

Set the factor '(18 + -1b)' equal to zero and attempt to solve: Simplifying 18 + -1b = 0 Solving 18 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -1b = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -1b = 0 + -18 -1b = 0 + -18 Combine like terms: 0 + -18 = -18 -1b = -18 Divide each side by '-1'. b = 18 Simplifying b = 18

Solution

b = {-16, 18}

See similar equations:

| 9-4(2x-1)-3x+2= | | 3x^4-21x^3+24x^2+23x-34=0 | | 20(7u-8v+3w)= | | 7z+2=-6 | | -7+2=6 | | 9x+16-6x=10-2x-19 | | 2p-3=p-5 | | 5a-16=25 | | v^2-10v+16= | | 4w-3x-y-5w+18x-7y= | | -6+[25+(-12)]=43 | | X^2+100+60-3x+30-4x=180 | | -6+[25+(-12)]=31 | | -13+2x=-52+13 | | -6+[25+(-12)]=7 | | -6+[25+(-12)]=19 | | 4=5+2x | | 5x+17-4x=-2-10 | | X/Y=7/11 | | 3x^2-(3m-2)x-(3m+1)=0 | | 1/3*1/3*1/3*1/3*a*a*b*b*c | | 5x-3y=106 | | 16+7yi=8x+i | | x-6=3(2x) | | f-5-3f=7 | | 2x+(x+1)=2 | | 2(4w+9)/4=-10 | | 5x/6-3/2=x/3 | | 0.5(7y+1)-3=8 | | 5(f-1)=25 | | 15m+2n-6m+8n= | | 15x^2+42x=9 |

Equations solver categories